In Vitro Effect of Two Alcohol-Free and Alcohol-Containing Listerine Mouthwashes on the Shear Bond Strength of Orthodontic Brackets : Alcohol-free vs. Alcohol Listerine: Effect on Bracket Bond Strength - Toodehzaeim, Mohammad Hossein; Toodehzaeim, Pedram; Zadbin, Fariba (Regeneration, Reconstruction & Restoration (Triple R), 2024)
Background and objectives: This study aimed to investigate the in vitro effects of two Listerine mouthwashes—one alcohol-free and the other containing alcohol—on the shear bond strength of orthodontic brackets. Materials and methods: This experimental study was accomplished on 45 healthy human premolars that were extracted for orthodontic treatment. The teeth after mounting in acrylic blocks were bonded with metal orthodontic brackets (MBT/0.22) by composite and randomly divided into three groups: (1) alcohol-containing Listerine mouthwash (ACLM), (2) alcohol-free Listerine mouthwash (AFLM), (3) artificial saliva (control). 15 samples were placed in each group. After keeping teeth in the solutions, the shear bond strength of orthodontic brackets was measured by the universal testing machine at a speed of 1 mm/min, and the information was compared using one-way ANOVA analysis. Results: In general, the average shear bond strength of 45 premolars was evaluated as 20.92±6.8 MPa. Shear bond strength was reported as 18.32±7.33 MPa in the first group (Listerine containing alcohol), 22.33±7.27 MPa in the second group (Listerine without alcohol), and 22.22±5.27 MPa in the third group (control group). The highest and lowest mean shear bond strength of the bracket to the tooth surface were shown in the alcohol-free Listerine and the alcohol-containing Listerine groups, respectively. The results of one-way ANOVA showed no statistically significant difference in terms of shear bond strength among the three groups (P-value˃0.05). Conclusion: Since both alcohol-containing and alcohol-free Listerine mouthwashes are effective in reducing viral and oral microbial loads, the lack of significant impact on bracket bond strength supports the recommendation of these mouthwashes in orthodontic practice.